Cell wall-related genes and lignin accumulation contribute to the root resistance in different maize (Zea mays L.) genotypes to Fusarium verticillioides (Sacc.) Nirenberg infection - Quiroz-Figueroa, Francisco Roberto; Cruz-Mendívil, Abraham; Ibarra-Laclette, Enrique; García-Pérez, Luz María; Gómez-Peraza, Rosa Luz; Hanako-Rosas, Greta; Ruíz-May, Eliel; Santamaría-Miranda, Apolinar; Singh, Rupesh Kumar; Campos-Rivero, Gerardo; García-Ramírez, Elpidio; Narváez-Zapata, José Alberto (Frontiers in Plant Science, 2023)
The fungal pathogen Fusarium verticillioides (Sacc.) Nirenberg (Fv) causes considerable agricultural and economic losses, and is harmful to animal and human health. Fv can infect maize throughout its long agricultural cycle, and root infection drastically affects maize growth and yield. The root cell wall is the first physical and defensive barrier against soilborne pathogens such as Fv. This study compares two contrasting genotypes of maize (Zea mays L.) that are resistant (RES) or susceptible (SUS) to root Fv infection by using transcriptomics, fluorescence, and scanning electron microscopy analyses. Seeds were infected with a highly virulent local Fv isolate. Although Fv infected both the RES and SUS genotypes, infection occurred faster in SUS, notably showing a difference of three to four days. In addition, root infections in RES were less severe in comparison to SUS infection. Comparative transcriptomics (rate +Fv/control) were performed seven days after inoculation (DAI). The analysis of differentially expressed genes (DEGs) in each rate revealed a total of 733 and 559 transcripts that were significantly (P ≤ 0.05) up- and downregulated in RES (+Fv/C) and SUS (+Fv/C), respectively. KEGG pathway enrichment analysis identified coumarin and furanocoumarin biosynthesis, phenylpropanoid biosynthesis, and plant-pathogen interaction pathways as being highly enriched with specific genes involved in cell wall modifications in RES genotype, whereas SUS genotype mainly displayed a repressed plant-pathogen interaction pathway and did not show any enriched cell wall genes. Analysis of DEG abundance made it possible to identify transcripts involved in response to abiotic and biotic stresses, biosynthetic and catabolic processes, pectin biosynthesis, phenylpropanoid metabolism, and cell wall biosynthesis and organization. Root histological analysis in RES showed an increase in lignified cells at the sclerenchymatous hypodermis zone during Fv infection. These differences in the cell wall and lignification could be related to an enhanced degradation of the root hairs and the epidermis cell wall in SUS, as was visualized by SEM. These findings reveal that components of the root cell wall are important against Fv infection and possible others soilborne phytopathogens.